Prevalence of insomnia and sleep pattern among MBBS students of Stanley Medical College, Chennai - Kumar, R. Senthil; Kumar, K. Sathish (International Journal Of Community Medicine And Public Health, 2019)
Background: Having a healthy behavior and physiology is impossible without normal sleep pattern. Between the ages 18 and 25, people are prone to sleep disturbances. College life, which mostly occurs during this ages also affects the sleep pattern. Methods: This is a descriptive cross sectional study conducted among MBBS students of Stanley Medical College during august to September 2009. About 300 students were randomly selected using table of random numbers. Data was collected using a questionnaire and entered in SPSS version 16 software. Analysis was done using chi-square test. P value of less than 0.05 was taken as statistically significant. Results: Prevalence of insomnia is found to be 37% and is significantly higher among males. Disturbed sleep is higher among males. Conclusions: Prevalence of insomnia is 37% and is significantly higher among males. About 26.3% of the participants had disturbed sleep.